2020
DOI: 10.3390/geosciences10040154
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Attribute Analysis Using Coherency and Ant-Tracking Techniques for Fault and Fracture Detection in La Florida Anticline, Llanos Foothills, Colombia

Abstract: We present techniques to reduce noise and enhance seismic quality, making possible the first multi-attribute analysis of a 3D seismic volume in the Llanos Foothills (La Florida anticline) of Colombia using coherency and ant-tracking techniques for fault and fracture detection. The results could help reduce risk in models of reservoir fracture porosity and permeability. The dominant fracture strike direction in the studied seismic volume (La Florida anticline) is NE–SW (055 ± 20°), parallel to the structural st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 31 publications
(50 reference statements)
0
7
0
Order By: Relevance
“…Several studies have shown the applicability of 3D seismic data for fracture analysis (Jaglan et al, 2015;Fang et al, 2017;Albesher et al, 2020;Boersma et al, 2020;Loza Espejel et al, 2020;Méndez et al, 2020), which can be used to address the often-raised question of scalability of reservoir properties (e.g. Lake & Srinivasan, 2004;Li et al, 2019), i.e., can information regarding fracture properties be transferred from the well scale to the seismic scale and vice versa?…”
Section: Ant-track Based Fracture Orientation Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…Several studies have shown the applicability of 3D seismic data for fracture analysis (Jaglan et al, 2015;Fang et al, 2017;Albesher et al, 2020;Boersma et al, 2020;Loza Espejel et al, 2020;Méndez et al, 2020), which can be used to address the often-raised question of scalability of reservoir properties (e.g. Lake & Srinivasan, 2004;Li et al, 2019), i.e., can information regarding fracture properties be transferred from the well scale to the seismic scale and vice versa?…”
Section: Ant-track Based Fracture Orientation Analysismentioning
confidence: 99%
“…Furthermore, Wang et al (2016) used seismic attributes to describe the reef growth and the evolution of channel systems for Eocene carbonates in the Sirte Basin in Libya. Edge-or discontinuity detection attributes, like variance and chaos, have been used to conduct a small-scale seismic-based fracture analysis (Jaglan et al, 2015;Williams et al, 2017;Albesher et al, 2020;Boersma et al, 2020;Loza Espejel et al, 2020). Nonetheless, seismic data lacks the high vertical resolution of well and outcrop data.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For the automatic extraction of fault lines and planes, ant tracking [10] can be used to extract fault lines based on curvature [11,12], chaos [13][14][15], and the coherence cube [16,17]. However, many parameters need to be considered for the ant tracking method, and adjustments to these parameters substantially affect the accuracy of fault detection.…”
Section: Introductionmentioning
confidence: 99%